Compact Triple-Band Orthogonal MIMO Antenna - Chandel, Richa; Kaundal, Shalu; Singh, Abhay; Kumar, Abhishek; Kumar, Saurab (Journal of Ubiquitous Computing and Communication Technologies, 2024)
The study proposes a compact triple-band orthogonal multiple-input multiple-output (MIMO) antenna design intended for operation in three distinct frequency bands: C band downlink (3.7-4.6 GHz), Wi-Fi 6E (6.1-7.2 GHz), and X band (8.4-10.1 GHz). The proposed antenna configuration incorporates four radiating elements with partially ground planes strategically arranged to achieve isolation between the bands and maintain desirable radiation characteristics across all three bands. The antenna is designed on a flame-retardant FR-4 substrate with a compact size of 30 mm x 30 mm, making it suitable for integration into various multi-band wireless devices. The proposed antenna can be used in applications such as wireless communication, satellite communication, and radar systems.
Keywords: MIMO; Multiband Antenna; U-shaped slot; Triple-band